Leveraging Ceres to Gain Insights into the Candidate Ocean Worlds of Umbriel and Oberon That Orbit Uranus - Jennifer E. C. Scully; C. Adeene Denton; Julie C. Castillo-Rogez; Michael M. Sori; Erin J. Leonard; Chloe Beddingfield; Richard Cartwright; Catherine M. Elder; Karl L. Mitchell; Tom A. Nordheim (The Planetary Science Journal)
Ceres, located in the asteroid belt, exhibits intriguing parallels with two of the large Uranian satellites: Umbriel and Oberon. These similarities include size, bulk compositions, and dominantly radiogenic internal heat sources. We identify morphologically similar features on Ceres, Umbriel, and Oberon and introduce new formation hypotheses, to consider alongside those that already exist, for the following two morphological features: (1) Brines from an impact-induced melt reservoir, potentially replenished by a subsurface ocean, may have formed the bright deposit in Wunda crater, on Umbriel, which we present as a new hypothesis alongside the previously proposed cold-trapped CO _2 ice deposit and cryovolcanism hypotheses. (2) A slurry of brine and solids, also potentially sourced from a subsurface ocean, may have formed the unnamed mountain on Oberon as a cryovolcanic dome, which we present as an additional possibility alongside the previously proposed impact crater central peak, tectonic feature, and remnant equatorial ridge hypotheses. We identify the data that could be collected by a future mission to test these hypotheses, in particular panchromatic images of at least 1 km pixel ^−1 and spatially resolved spectra in the infrared of at least 8 km pixel ^−1 . Future observations such as these would contribute to the overall understanding of the evolution of these candidate ocean worlds and their potential habitability.